Temperature analysis of ZnO/p-Si heterojunction using thermionic emission model - Hasim, H.; Sultan, S. M.; Mohamad, A. (International Journal of Engineering & Technology, 2018)
Two ZnO/p-Si heterojunction diode structures are modeled based on thermionic emission in numerical computation environment, and their current-voltage characteristics were validated in Spice with 500 Î© and 5 kÎ© load resistance. Both structures are differentiated based on thickness, metal size, and doping concentration. Parameters extracted such as barrier height, ideality factor, activation energy, series resistance, and shunt resistance are studied towards temperature-dependent study from 300 K to 673 K. Structure 1 proved to be exhibiting lower barrier height , series resistance and shunt resistance while structure 2 has lower ideality factor, activation energy, and turn on voltage. Modeling the ideality factor of structure 2 predicts a value of 0.25 at 673 K. Meanwhile, the turn on voltage of structure 2 is shown to achieve 0.8 V at room temperature. Barrier heights for structure 1 are reported to increase from 0.68 eV to 1.17 eV when temperature varies from 300 K to 673 K but series resistance and shunt resistance decreases with temperature.